Analysis of the Tradition of Reciprocating Pantun in the Marriage Party of the Malay Society in Ujung Kubu Village, Nibung Hangus District, Batu Bara Regency - Wan Nurul Atikah Nasution; Eva Mizkat; Dailami Dailami; Heni Subagiharti (Budapest International Research and Critics University, 2022)
The purpose of the study was to describe the tradition of reciprocating rhymes in the wedding party of the Malay community in Ujung Kubu Village. This research uses descriptive qualitative method. Descriptive data is data in the form of words, pictures, and not numbers (Moleong, 2016:11). This researcher took place in Ujung Kubu Village, Nibung Hangus District, Batu Bara Regency. The distance from Asahan University (UNA) to Batubara is approximately 67 km. The results of the study indicate that pantun in Malay people's lives is a means to convey moral messages which are full of noble values of religion, culture and social norms of society. The event of replying to the doorstop opening poem ended with a closing greeting from each of the bride and groom, not to forget the two families apologized to each other for possible mistakes and mistakes during the event, the event ended with a closing greeting. Malay people really like rhyming, from the past until now pantun has always been a tradition of the Malay community, it can even be said that the Malay community used to speak with rhymes. Pantun, especially in Malay society, is used as a means of communication to convey intentions, thoughts, opinions or advice and teaching. Pantun has pressure, acceptance and rhythm because rhymes contain aesthetic value, so at this time the tradition of reciprocating rhymes is still ongoing in the Malay community in Ujung Kubu Village, Nibung Hangus District, Batubara Regency in wedding parties..